Understanding Preoperative Breast Satisfaction among Patients Undergoing Mastectomy and Immediate Reconstruction: BREAST-Q Insights. Issue 6 (29th November 2021) - Shamsunder, Meghana G.; Polanco, Thais O.; McCarthy, Colleen M.; Allen, Robert J.; Matros, Evan; Coriddi, Michelle; Mehrara, Babak J.; Pusic, Andrea; Nelson, Jonas A.
Abstract : Background: This study aims to present normative values for satisfaction with breasts among preoperative breast reconstruction patients as assessed using the BREAST-Q instrument and to delineate factors associated with preoperative breast satisfaction. Methods: A retrospective analysis of prospectively collected data was performed examining women undergoing postmastectomy breast reconstruction at a tertiary care center who preoperatively completed the BREAST-Q from 2010 to 2017. Because breast satisfaction scores were nonnormally distributed, scores were categorized into quartiles for analysis. Patient- and treatment-level variables were tested in a multivariable ordinal logistic regression model as predictors of breast satisfaction. Preoperative satisfaction was also tested for association with choice of reconstructive modality. Results: Among 1306 postmastectomy reconstruction patients included in the study, mean preoperative Satisfaction with Breasts score was 61.8 ± 21.5 and the median score was 58.0 (interquartile range, 48 to 70). Factors associated with significantly lower preoperative satisfaction included history of psychiatric diagnosis, preoperative radiotherapy, marital status (married), and higher body mass index. Factors associated with significantly higher scores were malignancy (localized tumor), medium bra size (B to C cup), and self-identification as black. Preoperative breast satisfaction was lower among patients who elected autologous reconstruction than among those with implant reconstruction ( p < 0.001). Conclusions: Preoperative breast satisfaction is influenced by multiple factors. Understanding these factors may improve preoperative counseling and expectation management for patients who undergo postmastectomy breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.